2022
DOI: 10.3389/fmars.2022.973801
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven changes to taste and aroma determining metabolites in an economically valuable portunid (Portunus armatus) have implications for future harvesting

Abstract: The effects of climate change on the distribution and biology of fisheries species have received substantial attention, but quantitative assessments of changes to taste and aroma determining compounds remain limited—despite sensory quality being a key driver of demand for most harvested species. Utilising the economically important blue swimmer crab (Portunus armatus), we tested the effects of temperature and salinity treatments aligned with near-future climate change projections on volatile and non-volatile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…It has been increasingly recognized that the global climate change is having a signi cant adverse effect on coastal ecosystems (Vaughan, 2019;Shalders et al, 2023). Previous investigations have demonstrated that rising temperatures have signi cant impact on a variety of marine groups, including crustaceans, bivalves, gastropods and teleosts (Tate et al, 2017;Anacleto et al, 2014;Lemasson et al, 2019;Champion et al, 2022). Recent reports demonstrated that the greenhouse effect could raise seasurface temperatures by 1-10°C during this century, and thus, the great recovery function of the marine microbial fauna in the long-term evolution will meet a new challenge in the changing marine environment with continuous warming (Hutchins and Fu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been increasingly recognized that the global climate change is having a signi cant adverse effect on coastal ecosystems (Vaughan, 2019;Shalders et al, 2023). Previous investigations have demonstrated that rising temperatures have signi cant impact on a variety of marine groups, including crustaceans, bivalves, gastropods and teleosts (Tate et al, 2017;Anacleto et al, 2014;Lemasson et al, 2019;Champion et al, 2022). Recent reports demonstrated that the greenhouse effect could raise seasurface temperatures by 1-10°C during this century, and thus, the great recovery function of the marine microbial fauna in the long-term evolution will meet a new challenge in the changing marine environment with continuous warming (Hutchins and Fu, 2017).…”
Section: Introductionmentioning
confidence: 99%